Size-dependent optical absorption of Cu2ZnSn(Se,S)4 quantum dot sensitizers from ab initio many-body methods - Koerbel, Sabine; Boulanger, Paul; Blase, Xavier; Marques, Miguel A. L.; Botti, Silvana (European Physical Journal B, 2018)
Quantum-dot sensitized solar cells are an exciting technology because they allow to overcome the efficiency limit of single-junction solar cells. The tunability of their band gap with quantum-dot size allows to make multi-junction solar cells with optimized band gaps, moreover using simple production techniques. Here, we study quantum-dot sensitizers made of the earth-abundant photovoltaic absorbers Cu2ZnSnS4 and Cu2ZnSnSe4 (CZTS). Using many-body perturbation theory (GW and the Bethe–Salpeter equation) and time-dependent density-functional theory, we calculate the dependence of the photoemission and optical band gap on the quantum-dot size, accounting for excitonic effects. Our study completes the existing knowledge about quantum confinement in CZTS nanocrystals, for which experimental data are sparse and provide the power law that describes the dependence of the optical gap on the quantum-dot size.
CRIS-Team Scopus Importer:2023-04-20